"Pivot" Toward Asia: The Strategic Direction of Russia's Foreign Policy Concept in a Changing Balance of Powers - Elena Yu. Litsareva (Centre for Behaviour and Wellness Advocacy, 2015)
The article examines some reasons of the "Russia's pivot" toward Asia at the turn of the XX-XXI centuries. The Asian policy of the Russia was starting to change at the second half of the 1990s. Russia conducted its policy at the East Asia in a view of the changed balance of national interests, regardless of the ideological considerations and attached a special importance to the economic cooperation. Developing the external political concept and determining the priority areas for development, Russia has had to reckon with the objective processes, occurring in the world. Russia, as the "Eurasian" power, building relations with the Asia-Pacific countries, was to have a vital task - to raise the political and economic cooperation with the Asia-Pacific region to the level, achieved by Russia in Europe. Gradually, the East Asia has become the priority strategic direction of the Russia positioning in the world. For a long time it was thought that using its geostrategic position, Russia could be an important factor in the global political and economic system, linking Europe and Asia-Pacific markets. Russia Federation supported the East Asia countries in ensuring regional security and stability. Analysis of the Asia-Pacific regional political situation shows that there are significant changes here and these changes are largely connected with the significant changes in the global balance of powers. In the course of the Ukrainian events (spring 2014) and entering the West economic sanctions against Russia in connection with the accession of the Crimea, Russian "pivot" toward Asia, in particular the East Asia, looks entirely justified and reasonable.